Highly efficient photocatalytic performance of dye-sensitized K-doped ZnO nanotapers synthesized by a facile one-step electrochemical method for quantitative hydrogen generation - Rouhi, J. (Springer, 2020)
The different morphologies of K-doped ZnO nanostructures were successfully synthesized by a facile one-step electrochemical method using control of the current density. Field emission electron microscope images showed various morphologies and aspect ratios due to change in the value of applied current densities. Photoluminescence and UV-visible spectrometers showed that change in current densities leads in different level of defects and band gap shifting. The photocurrent responses reveal that the photocurrent intensity increases as K-doped ZnO surface morphology tends to taper on the application of 0.5Â mAÂ cmâ2 current density. The maximum degradation rate of methylene blue was attained to be 99.3 within the 60Â min using K-doped ZnO nanotapers which was much higher than the values found in previous studies. The highest photocatalytic H2 evolution activities were obtained in the applied current density of 0.5Â mAÂ cmâ2 in comparison to other samples. These results indicate that doping and controllable morphology are effective and facile methods to improve the photocatalytic features of ZnO by boosting the absorption of light. Â© 2020, Springer-Verlag GmbH Germany, part of Springer Nature.